Popular treatment modalities in the management of sacroiliac joint dysfunction - E.D. Watson (AOSIS, 2012)
The treatment of sacroiliac joint (SIJ) dysfunction presents aclinical challenge for physiotherapists. The aim of this study was to investigatecurrent physiotherapy practise in the management of acute and chronic SIJdysfunction. A chart audit of 677 SIJ patient reports (N=677) from 75 differentprivate physiotherapy practises were analysed to determine the following:(1) the prevalence of the use of exercise therapy, and the types of exercise used inthe management of SIJ dysfunction, and (2) the prevalence of other therapeuticmodalities utilised alongside exercise therapy. The results of the study indicated thatuse of exercise therapy, specifically stretches and mobility exercises, is a popular treatment choice by physiotherapists.Joint mobilisations and soft tissue massage often accompanied exercise. Despite research outcomes suggesting both astrengthening and stabilisation program for the lumbo-pelvic complex, these approaches were less favoured.